Activation of the Pseudomonas aeruginosa Type III Secretion System Requires an Intact Pyruvate Dehydrogenase aceAB Operon - Dacheux, Denis (American Society for Microbiology, 2002)
Pseudomonas aeruginosa clinical cystic fibrosis isolate CHA was mutagenized with Tn5Tc to identify new genes involved in type III secretion system (TTSS)-dependent cytotoxicity toward human polymorphonuclear neutrophils. Among 25 mutants affected in TTSS function, 14 contained the insertion at different positions in the aceAB operon encoding the PDH-E1 and -E2 subunits of pyruvate dehydrogenase. In PDH mutants, no transcriptional activation of TTSS genes in response to calcium depletion occurred. Expression in trans of ExsA restored TTSS function and cytotoxicity.